Implementasi Program Keluarga Harapan (PKH) Dalam Meningkatkan Kesejahteraan Masyarakat Dalam Perspektif Ekonomi Syariah: Studi Di Desa Mendalo Indah, Kec. Jambi Luar Kota, Kab. Muaro Jambi, Prov. Jambi - Fadila Mawaddah; Addiarrahman Addiarrahman; Fauzan Ramli (Master Manajemen, 2023)
The Family Hope Program (PKH) is a social protection program that provides non-cash assistance to poor families designated as Beneficiary Families (KPM). PKH is a program based on poor families, so the main targets are economically disadvantaged families. PKH is an effort directed towards the formation and human resources focus on aspects of education, health, and social welfare. This research is entitled "Implementation of the Family Hope Program (PKH) in Improving Community welfare in the Islamic Economic Initiative". The purpose of this study is to find out what the Family Hope Program (PKH) is in providing social welfare to the community, find out how the implementation of the Family Hope Program (PKH) in providing social protection to the community, and find out what are the driving factors and inhibiting factors in implementing the Family Hope Program (PKH). This research uses a qualitative method with a descriptive approach and in sampling researcher used sample selection techniques with the provision of characteristics and characteristics of objects in the study, as for data collection techniques, namely through observation, interviews, and documentation. The results showed that the social protection provided by PKH to the community was in the fields of education, health, and social welfare. The implementation of PKH in Mendalo Indah Village goes through several stages, the first starting from the initial meeting stage, the second stage of entering data into the Management information system, the third stage of payment, and the last stage of commitment verification. The driving and inhibiting factors of PKH carried out in Mendalo Indah Village are that although it has not been fully implemented perfectly, the community admits that this program has helped and provided relief to the community.